Biological and clinical characteristics of the European Friedreich's Ataxia Consortium for Translational Studies (EFACTS) cohort: a cross-sectional analysis of baseline data. Issue 2 (February 2015) - Reetz, Kathrin; Dogan, Imis; Costa, Ana S; Dafotakis, Manuel; Fedosov, Kathrin; Giunti, Paola; Parkinson, Michael H; Sweeney, Mary G; Mariotti, Caterina; Panzeri, Marta; Nanetti, Lorenzo; Arpa, Javier; et al.
Summary Background Friedreich's ataxia is a rare autosomal recessive neurodegenerative disorder. Here we report cross-sectional baseline data to establish the biological and clinical characteristics for a prospective, international, European Friedreich's ataxia database registry. Methods Within the European Friedreich's Ataxia Consortium for Translational Studies (EFACTS) framework, we assessed a cohort of patients with genetically confirmed Friedreich's ataxia. The primary outcome measure was the Scale for the Assessment and Rating of Ataxia (SARA) and secondary outcome measures were the Inventory of Non-Ataxia Signs (INAS), the performance-based coordination test Spinocerebellar Ataxia Functional Index (SCAFI), the neurocognitive phonemic verbal fluency test, and two quality-of-life measures: the activities of daily living (ADL) part of the Friedreich's Ataxia Rating Scale and EQ-5D. The Friedreich's ataxia cohort was subdivided into three groups: early disease onset (≤14 years), intermediate onset (15–24 years), and late onset (≥25 years), which were compared for clinical characteristics and outcome measures. We used linear regression analysis to estimate the annual decline of clinical outcome measures based on disease duration. This study is registered with ClinicalTrials.gov, number NCT02069509. Findings We enrolled 592 patients with genetically confirmed Friedreich's ataxia between Sept 15, 2010, and April 30, 2013, at 11 sites in seven European countries. Age of disease onset was inversely correlated with the number of GAA repeats in the frataxin (FXN) gene: every 100 GAA repeats on the smaller repeat allele was associated with a 2·3 year (SE 0·2) earlier onset. Regression analyses showed significant estimated annual worsening of SARA (regression coefficient 0·86 points [SE 0·05], INAS (0·14 points [0·01]), SCAFI Z scores (−0·09 [0·01]), verbal fluency (−0·34 words [0·07]), and ADL (0·64 points [0·04]) during the first 25 years of disease; the regression slope for health-related quality-of-life state from EQ-5D was not significant (−0·33 points [0·18]). For SARA, the predicted annual rate of worsening was significantly higher in early-onset patients (n=354; 1·04 points [0·13]) and intermediate-onset patients (n=137; 1·17 points [0·22]) than in late-onset patients (n=100; 0·56 points [0·10]). Interpretation The results of this cross-sectional baseline analysis of the EFACTS cohort suggest that earlier disease onset is associated with larger numbers of GAA repeats and more rapid disease progression. The differential estimated progression of ataxia symptoms related to age of onset have implications for the design of clinical trials in Friedreich's ataxia, for which SARA might be the most suitable measure to monitor disease progression. Funding European Commission.